Paradigma Filsafat Pendidikan Islam dalam Perspektif Postmodern dan Rekonstruktivisme - Puji Ningsih; Juni Erpida (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This paper examines the paradigm of Islamic philosophy of education from postmodern and reconstructivist perspectives as an effort to construct a critical, humanistic, and transformative educational framework. The dominance of modernism, characterized by instrumental rationality and an excessive emphasis on technical efficiency, has contributed to spiritual crises, alienation, and dehumanization within educational practices. As a response, postmodernism challenges rational absolutism and creates space for spirituality, intercultural dialogue, ethical reflection, and value pluralism. In this context, Islamic education possesses significant potential to function as a liberating and enlightening movement through the integration of tawhid-based principles, human dignity, and social justice. Meanwhile, reconstructivism views education not merely as the transmission of knowledge but as a dynamic process of social reconstruction aimed at fostering ethical awareness and collective responsibility. This study proposes a synthesis between Islamic philosophical foundations and contemporary thought—postmodernism, critical theory, and reconstructivism—to formulate a renewed and globally relevant direction for Islamic education in the modern era.